The effect of section 2(1) of the Interim Protection of Informal Land Rights Act 31 of 1996 on the granting of a mining right in terms of section 23 and the dispute resolution processes in terms of section 54 of the Mineral and Petroleum Resources Development Act 28 of 2002. - Gerber, Leon (University of Pretoria, 2021)
Dissertation (LLM) University of Pretoria, 2021.